Boomerang Young Adults in Seoul, South Korea: Residential Pathways, Health and Social Attitudes - Gum‐Ryeong Park; Jiawei Wu (Population, Space and Place, 2026)
ABSTRACT Leaving the parental home is a key transition to adulthood. However, recent sociodemographic changes have produced more diverse residential pathways such as delayed home‐leaving or returning to the parental home (‘boomerang movers’). While prior research has focused on the characteristics and determinants of these patterns, few studies have examined how various residential pathways are related to trajectories of health and social attitudes in Korea. We used longitudinal data from the annual Seoul Young Adult Panel Study (2021–2024) of individuals aged 18–34 interviewed ≥ 2 waves ( n = 4895) and identified 4 residential pathways: persistent coresidence, persistent independence, boomerang and transition into independence. Outcomes were self‐rated health, suicidal ideation, social outlook (expectations regarding Korea's future relative to the present) and perceived social fairness. Mixed‐effects models were then estimated to examine differences in levels and rates across pathways. Compared with persistent coresidence, persistent independence was associated with a lower probability of reporting suicidal ideation at baseline and slower decreases over time. Boomerang adults had lower self‐rated health and higher suicidal ideation at baseline. However, they showed greater improvements over time: faster gains in self‐rated health, a more rapid decline in the likelihood of reporting suicidal ideation, larger increases in perceived social fairness and a less pronounced decline in social outlook. No significant differences were observed for the transition into independence group. Overall, residential pathways are linked to distinct trajectories of health and social attitudes during emerging adulthood. Boomerang living reflects initial disadvantages, gradual improvements and adaptation among urban young adults.